Pengaruh Budaya Ruwatan Bumi Dalam Meningkatakan Budaya Gotong Royong di Dusun 1 Desa Parakan Garokgek - Yudi Maulidin; Siti Khodijah; Achmad Rofi’i; Faisal Ihsan; Tri Dian Nurhalimah (Universitas Maritim AMNI Semarang, 2023)
Ruwatan Bumi educates people to have high morality, by developing an attitude of mutual cooperation, tolerance, honesty, respect for others, the environment and nature. Methods based on interview observations and scientific journals are then strengthened by sources relevant to the research. The information collected is then described with the urgency of writing, about the dynamics of mutual cooperation and shared community habits. The data collection method involves gathering information with community leaders, and preparing a systematic analysis by the author. The people of Hamlet 1, Parakan Garokgek Village, Kiarapedes Subdistrict, explained that there are several traditions of Ruatan Bumi that have several connections with God, Nature and Humans.